Indonesia’s National Energy Supply Chain Resilience Strategy: Comparative Lessons and Policy Recommendations within the Asta Cita Framework - Akbar, Muhammad Amri; Baihaqi, Muhammad; Maulana, Ikmal (Journal of Social Growth and Development Studies, 2026)
Energy supply chain resilience constitutes the foundation of economic sovereignty explicitly mandated by the Second Asta Cita of the Prabowo-Gibran Administration 2024–2029. This article analyses the structural vulnerabilities of Indonesia's energy supply chain—80.58% LPG import dependency, significant fuel imports, 20–25 days of operational reserve, and a US$20.4 billion oil-and-gas trade deficit in 2024—and constructs a resilience framework through comparative learning from Brazil (Proálcool), India (Production Linked Incentive scheme), Japan (254-day strategic reserve), and Germany (Energiewende sequencing failure 2022). The study employs comparative-historical analysis and systematic literature review covering 30 academic references and official policy documents. Findings demonstrate that resilience requires integration of Christopher and Peck's (2004) four pillars with APERC's (2007) 4A energy security framework, operationalised through five strategic pathways: (1) establishing a 90-day Strategic Petroleum Reserve; (2) replicating India's renewable manufacturing incentive package; (3) ensuring biofuel policy consistency across regimes; (4) institutionalising annual energy supply chain stress-tests; and (5) properly sequencing the transition by maintaining gas and geothermal baseload. The article proposes a Conceptual Framework for National Energy Supply Chain Resilience (KR-RPEN) as a context-specific theoretical synthesis.